Juridical Review of Online Fraud Convictions Against Job Vacancies - Safara, Intan (Journal of Law and Social Politics, 2024)
Background: The growth of global tourism has encouraged the emergence of the Muslim-Friendly Tourism concept as an effort to accommodate the specific needs of Muslim travelers. Differences in social, cultural, and regulatory contexts across countries lead to variations in how this concept is understood and implemented. Therefore, it is important to examine the meaning and application of Muslim-Friendly Tourism from the perspective of Indonesian Muslim tourists, who represent one of the largest Muslim travel markets worldwide. Objective: This study aims to compare the meaning and implementation of the Muslim-Friendly Tourism concept in the United Arab Emirates and Japan from the perspective of Indonesian Muslim tourists. Methods: This research adopts a qualitative approach using interviews and literature review as data collection methods. Interviews were conducted with Indonesian Muslim tourists who had visited the United Arab Emirates, Japan, or both countries. Literature review was employed to support and enrich the analysis of issues related to Muslim-Friendly Tourism. Results: The findings indicate that the United Arab Emirates, as a globally open destination, provides various facilities including non-halal food and beverages, making Muslim-Friendly Tourism an important mechanism to ensure comfort for Muslim residents and tourists. Meanwhile, Japan has made efforts to accommodate the needs of Muslim tourists, although such facilities remain limited and are mainly concentrated in major cities and popular tourist destinations. This condition is generally well understood by Muslim travelers. Conclusion: Muslim-Friendly Tourism is perceived as a form of standardization that fulfills the essential needs of Muslim tourists and supports their comfort and safety while traveling. In both the United Arab Emirates and Japan, the concept plays a strategic role in enhancing the travel experience of Muslim tourists, although its implementation varies according to each country’s specific context and characteristics.